Utilization of maize cob biochar and rice husk charcoal as soil amendment for improving acid soil fertility and productivity - N Nurhidayati; M Mariati (Brawijaya University, 2014)
The decline in soil fertility in agricultural land is a major problem that causes a decrease in the production of food crops. One of the causes of the decline in soil fertility is declining soil pH that caused the decline in the availability of nutrients in the soil. This study aimed to assess the influence of alternative liming materials derived from maize cob biochar and rice husk charcoal compared to conventional lime to improve soil pH, soil nutrient availability and maize production. The experiment used a factorial complete randomized design which consisting of two factors. The first factor is the type of soil amendment which consists of three levels (calcite lime, rice husk charcoal and cob maize biochar). The second factor is the application rates of the soil amendment consisted of three levels (3, 6 and 9 tons ha-1) and one control treatment (without soil amendment) . The results of this study showed that the application of various soil amendment increased soil pH, which the pH increase of the lime application was relatively more stable over time compared to biochar and husk charcoal. The average of the soil pH increased for each soil amendment by 23% (lime), 20% (rice husk charcoal) and 23% (biochar) as compared with control. The increase in soil pH can increase the availability of soil N, P and K. The greatest influence of soil pH on nutrient availability was shown by the relationship between soil pH and K nutrient availability with R2 = 0.712, while for the N by R2 = 0.462 and for the P by R2 = 0.245. The relationship between the availability of N and maize yield showed a linear equation. While the relationship between the availability of P and K with the maize yield showed a quadratic equation. The highest maize yield was found in the application of biochar and rice husk charcoal with a dose of 6-9 t/ha. The results of this study suggested that biochar and husk charcoal could be used as an alternative liming material in improving acid soil fertility and productivity.